PERSEPSI MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS SURABAYA ANGKATAN 2014 DAN 2015 TERHADAP PROFESI AKUNTAN PUBLIK - Stella Levina Anggoro; Bonnie Soeherman (Perpustakaan Universitas Surabaya, 2018)
Public accountant is one of some career option for students majoring in accounting after completing their education. A public accountant is a profession that plays an important role for the business and economic, and also has a great responsibility to public. This study aims to determine the perceptions of students majoring in Accounting at University of Surabaya to public accountantprofession and their interests and considerations to decide their career as a public accountant. The object of this research is the students of year class 2014 and 2015 who have been at the final gradeof S1 Accounting major at University of Surabaya. In this study, the authors use qualitative research methods with an interpretive research paradigm. For data collection in this research is done through interview, observation, and document analysis. The results showed that students majoring Accounting at the University of Surabaya have positive and negative perceptions of the public accountant profession. The difference of perception is influenced by various factors both internal and external. Such perceptions also affect the interest of students to decide their career as public accountant. The result of the research shows that there is a considerable interest from University of Surabaya Accounting major students to the publicaccountant profession.